Effect of particle-size selectivity on quantitative X-ray dark-field computed tomography using a grating interferometer. (August 2017) - Bao, Yuan; Shao, Qigang; Hu, Renfang; Wang, Shengxiang; Gao, Kun; Wang, Yan; Tian, Yangchao; Zhu, Peiping
Abstract: According to the conclusion of Khelashvili et al. [Phys. Med. Biol. 51, 221 (2006)], the minus logarithm of the visibility ratio fulfills the line integral condition; consequently the scattering information can be reconstructed quantitatively by conventional computed tomography (CT) algorithms. Based on Fresnel diffraction theory, we analyzed the influence of particle-size selectivity on the performance of an X-ray grating interferometer (GI) applied for dark-field CT. The results state the signal-to-noise ratio (SNR) of dark-field imaging is sensitive to the particle size, which demonstrate that the X-ray dark-field CT using a GI can efficiently differentiate materials of identical X-ray absorption and help to choose optimal X-ray energy for known particle size, thus extending the application range of grating interferometer. Highlights: Propose a method to differentiate materials of identical X-ray absorption. Quantitatively reconstruct the dark-field CT image with specific particle-size. Extend the application range of grating interferometer.